2017
DOI: 10.1155/2017/9173090
|View full text |Cite
|
Sign up to set email alerts
|

Autotaxin-Lysophosphatidic Acid: From Inflammation to Cancer Development

Abstract: Lysophosphatidic acid (LPA) is a ubiquitous lysophospholipid and one of the main membrane-derived lipid signaling molecules. LPA acts as an autocrine/paracrine messenger through at least six G protein-coupled receptors (GPCRs), known as LPA1–6, to induce various cellular processes including wound healing, differentiation, proliferation, migration, and survival. LPA receptors and autotaxin (ATX), a secreted phosphodiesterase that produces this phospholipid, are overexpressed in many cancers and impact several f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 141 publications
4
93
0
Order By: Relevance
“…Previous studies have described a role for LPA and autotaxin, its main synthetic enzyme, in inflammatory processes (8,25,43,45). In line with this, we found that expression of LPA1 was To understand how LPA1 exerts its influence on the inflammatory component of MS and EAE, we examined infiltration and activation of immune cells.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Previous studies have described a role for LPA and autotaxin, its main synthetic enzyme, in inflammatory processes (8,25,43,45). In line with this, we found that expression of LPA1 was To understand how LPA1 exerts its influence on the inflammatory component of MS and EAE, we examined infiltration and activation of immune cells.…”
Section: Discussionsupporting
confidence: 78%
“…In the past years, the role of LPA in the pathogenesis of different immune-related diseases has been recognized. LPA dysregulation has been implicated in different inflammatory diseases, such as atherosclerosis (8), cancer (45), and MS (41) because of its effect on immune cells, of both the innate and adaptive immune systems (3,15,23). However, despite the growing knowledge in this field, many aspects of the role of LPA in immune-related pathogenesis remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…LPA is a bioactive phospholipid that stimulates the proliferation, migration, and survival of many cell types [24]. LPA has no membrane-perturbing effects and is water-soluble [25].…”
Section: Physiological Functions Of the Lpa-atx Axismentioning
confidence: 99%
“…Recently, LPA 1 receptor was discovered related to the proliferation and migration of GBM. In three GBM cell lines, LPA induces PKCα activation by LPA 1 , leading to nuclear translocation of kinases, increasing cell number and increasing cell viability [85,86].…”
Section: Lpar and Glioblastomamentioning
confidence: 99%